Alarming low physical activity levels in Chilean adults with disabilities during COVID-19 pandemic: a representative national survey analysis - Matías Henríquez; Rodrigo Ramirez-Campillo; Carlos Cristi-Montero; Raul Reina; Cristián Alvarez; Gerson Ferrari; Nicolas Aguilar-Farias; Kabir P. Sadarangani; Kabir P. Sadarangani (Frontiers Media S.A., 2023)
BackgroundPeople with disabilities usually face barriers to regularly engaging in physical activities. Estimating physical activity patterns are necessary to elaborate policies and strategies to facilitate active lifestyles, considering the particular access difficulties experienced by this population.PurposeThis study aimed (i) to describe the prevalence of physical activity levels and (ii) to examine the associations of physical activity levels with socio-demographic variables and type of disability in the 2020 Chilean National Physical Activity and Sports Habits in Populations with Disabilities (CNPASHPwD) survey during the coronavirus disease 19 (COVID-19) pandemic.MethodsCross-sectional data from 3,150 adults (18-99 years old), 59.8% female, were analyzed from November to December 2020. Self-reported age, gender, type of disability (i.e., physical, visual, hearing, intellectual, or mixed), socio-economic status, area and zone of residence, and physical activity levels (0 min/week, < 150 min/week, ≥ 150 min/week) were obtained.Results11.9% of the participants were classified as active (≥ 150 min/week), and 62.6% declared no involvement in physical activity. A larger proportion of females (61.7%) did not meet the current guidelines (≥ 150 min/week of physical activity) in comparison with males (p < 0.001). Participants with visual and hearing disabilities were more likely to be active than those with other types of disabilities. Those living in the central and southern regions of Chile were more likely to be physically active than those from the northern region. Also, older participants, women, and those from lower socio-economic statuses were less likely to meet the physical activity guidelines.ConclusionAlarmingly, nine out of ten participants were categorized as physically inactive, particularly women, older adults, and those with a low socioeconomic status. If the pandemic context moderated, the considerable prevalence of reduced physical activity levels deserves future exploration. Health promotion initiatives should consider these aspects, emphasizing inclusive environments and increasing opportunities to favor healthy behaviors, countering the COVID-19 effects.